Characterization of the HMA7 gene and transcriptomic analysis of candidate genes for copper tolerance in two Silene vulgaris ecotypes - Baloun, Jiri; Nevrtalova, Eva; Kovacova, Viera; Hudzieczek, Vojtech; Cegan, Radim; Vyskot, Boris; Hobza, Roman (Journal of plant physiology, 2014)
Silene vulgaris possesses ecotype-specific tolerance to high levels of copper in the soil. Although this was reported a few decades ago, little is known about this trait on a molecular level. The aim of this study was to analyze the transcription response to elevated copper concentrations in two S. vulgaris ecotypes originating from copper-contrasting soil types - copper-tolerant Lubietova and copper-sensitive Stranska skala. To reveal if plants are transcriptionally affected, we first analyzed the HMA7 gene, a known key player in copper metabolism. Based on BAC library screening, we identified a BAC clone containing a SvHMA7 sequence with all the structural properties specific for plant copper-transporting ATPases. The functionality of the gene was tested using heterologous complementation in yeast mutants. Analyses of SvHMA7 transcription patterns showed that both ecotypes studied up-regulated SvHMA7 transcription after the copper treatment. Our data are supported by analysis of appropriate reference genes based on RNA-Seq databases. To identify genes specifically involved in copper response in the studied ecotypes, we analyzed transcription profiles of genes coding Cu-transporting proteins and genes involved in the prevention of copper-induced oxidative stress in both ecotypes. Our data show that three genes (APx, POD and COPT5) differ in their transcription pattern between the ecotypes with constitutively increased transcription in Lubietova. Taken together, we have identified transcription differences between metallifferous and non-metalliferous ecotypes of S. vulgaris, and we have suggested candidate genes participating in metal tolerance in this species.
Keywords: databáze nukleových kyselin; Gene Expression Regulation, Plant; sekvenční analýza RNA; ekotyp; Copper; orgánová specificita; transkriptom; Cation Transport Proteins; měď; Tissue-specific transcription; Plant Roots; Organ Specificity; RNA, Plant; Transcriptome; rostlinné proteiny; kořeny rostlin; Ecotype; Sequence Analysis, RNA; Genes coding ROS-eliminating and Cu-transporting proteins; Gene Library; ATPasy transportující měď; Plant Proteins; regulace genové exprese u rostlin; RNA-Seq database; Plant Shoots; Copper-Transporting ATPases; Silene; Adenosine Triphosphatases; proteiny přenášející kationty; výhonky rostlin; genová knihovna; adenosintrifosfatasy; RNA rostlin; Databases, Nucleic Acid